Usulan Rute Optimal Distribusi Sampah Shift I Kota Sumbawa Besar Menggunakan Metode GVRP - Koko Hermanto; Eki Ruskartina (Eigen Mathematics Journal, 2018)
Generalized vehicle routing problem (GVRP), for each vertex of the graph is partitioned into vertex sets and called groups, it will be determined the optimal route given to each set group includes exactly one vertex of each group. Furthermore, the cluster generalized vehicle routing problem (CGVRP) was introduced which aims to determine the optimal route for each vertex for each cluster. The optimal route can be solved using the Djikstra Algorithm. The distribution of waste in the city of Sumbawa Besar is still considered to be less than optimal, so this system can be implemented by making direct connections between each polling station. This system produces the shortest route, travel details, distance between polling stations and travel costs.